An Onomastics Study of Theism and Sacrality in Ewe Anthroponymy - Horsu, Isaac; Akakpo, Imeta; Horsu Boakye, Salomey; Yao Agbenyo, Ebenezer (Journal of English Language Teaching and Applied Linguistics, 2026)
This paper set out to examine the theism and sacrality in the anthroponymy of the Ewe people (a proto-Kwa group of People who live presently in the southeastern part of Ghana, Togo, Benin, and the south-southwestern part of Nigeria as native speakers) and to examine whether their sacrality of the theistic knowledge is clearly portrayed in their names. Twenty-five names were sampled, out of which ten (10), which represent about 2/3 of the population, were analyzed. Drawing on cultural Linguistics theory by Palmer (1996), it was established that Ewes have always had theistic knowledge and portrayed that vividly in their names by showing the sacrality of the same in their anthroponymy, and concludes that Ewe names are not just names but are specific identifiers, pointers, and reminders of circumstances, and acknowledgements of God’s reign in the affairs of men.  Looking at some of the names that came up during the discussion and their connections with other names and subjects in the holy Bible, it is recommended that other researchers take a look at the claims of many oral traditions amongst the Ewe people which points to a strong link between the Ewe language and the ancient Hebrew roots of the names in the Bible to establish whether those claims are true or false. In addition, the study recommends that a more purposeful look should be made at the names of Ewes regarding the modernization and Anglicization of Ewe names, their spelling, meaning, and the impact of Christianity on modern Ewe names.